2021
DOI: 10.3390/geriatrics6030079
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and Gender Disparities in Healthy Ageing among People 50 Years and Older in South Africa

Abstract: Objective: this study aimed to determine the prevalence and correlates of healthy ageing in older adults living in the community in South Africa. Methods: the cross-sectional sample consisted of 3734 individuals (≥50 years) from the cross-sectional South African National Health and Nutrition Survey (SANHANES-1) in 2011–2012. Healthy ageing was assessed using a multidimensional concept, which includes five components: (1) absence of major illness, (2) absence of disability, (3) good mental health, (4) social en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Using a multidimensional concept of SA, we found that almost two in three older adults (≥50 years) (60.0%) in Thailand were successfully ageing; the figures were slightly lower for those ≥60 years (58.1%) and ≥65 years (56.3%). Thailand appears to have a prevalence of SA that is higher than in China ( N = 15,191; ≥65 years, 18.6%), Korea ( N = 4155; ≥65 years, 25.2%) [ 4 ], India ( N = 21,343; ≥65 years, 27.2%) [ 5 ], and South Africa ( N = 3734; ≥50 years, 36.6%) [ 6 ]. The SA component “no major illness” (≥50 years 92.3%; ≥65 years 90.0%) in this study was higher than in China (≥65 years, 75.1% [ 4 ], India (≥65 years; 83.3%) [ 5 ], and South Africa (≥50 years; 73.3%) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using a multidimensional concept of SA, we found that almost two in three older adults (≥50 years) (60.0%) in Thailand were successfully ageing; the figures were slightly lower for those ≥60 years (58.1%) and ≥65 years (56.3%). Thailand appears to have a prevalence of SA that is higher than in China ( N = 15,191; ≥65 years, 18.6%), Korea ( N = 4155; ≥65 years, 25.2%) [ 4 ], India ( N = 21,343; ≥65 years, 27.2%) [ 5 ], and South Africa ( N = 3734; ≥50 years, 36.6%) [ 6 ]. The SA component “no major illness” (≥50 years 92.3%; ≥65 years 90.0%) in this study was higher than in China (≥65 years, 75.1% [ 4 ], India (≥65 years; 83.3%) [ 5 ], and South Africa (≥50 years; 73.3%) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thailand appears to have a prevalence of SA that is higher than in China ( N = 15,191; ≥65 years, 18.6%), Korea ( N = 4155; ≥65 years, 25.2%) [ 4 ], India ( N = 21,343; ≥65 years, 27.2%) [ 5 ], and South Africa ( N = 3734; ≥50 years, 36.6%) [ 6 ]. The SA component “no major illness” (≥50 years 92.3%; ≥65 years 90.0%) in this study was higher than in China (≥65 years, 75.1% [ 4 ], India (≥65 years; 83.3%) [ 5 ], and South Africa (≥50 years; 73.3%) [ 6 ]. Similarly, the prevalence of the SA component “without disability” in Thailand was higher than in China, Korea, India, and South Africa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethnic differences have been documented in ageing and comorbidities relating to mental health, cardiovascular and respiratory diseases, and mortality, disadvantaging migrants compared to the host populations in Europe (Kristiansen, Razum et al 2016, Markides andRote 2018). Studies have also shown that these health disparities vary by sex, gender, and socioeconomic status with ageing (Sialino, Schaap et al 2019, Muilwijk, Callender et al 2021, Pengpid and Peltzer 2021, Sialino, van Oostrom et al 2021, Stephens, Szabó et al 2022). However, most healthy ageing research has explored ethnic differences in populations aged 50 years or over (Stuart 2010, Sachdev, Lipnicki et al 2013, Asamane, Greig et al 2020, Pengpid and Peltzer 2021, Peterson, George et al 2021, Hernandez Saucedo, Whitmer et al 2022, Meza, Peterson et al 2022, Stephens, Szabó et al 2022).…”
Section: Introductionmentioning
confidence: 99%